Influence of Crack on Concrete Damage in Salt-Freezing Environment - Guangyan Liu; Song Mu; Jingshun Cai; Deqing Xie; Ying Zhou; Xiaocheng Zhou (Advances in Materials Science and Engineering)
The damage development trend of concrete with cracks in salt-freezing environment is systematically studied. The cracks are also tested in intact concrete for comparison, and crack characterization is introduced. The mass loss, the relative dynamic elastic modulus, and the change of crack width are analyzed. Results show that the crack width increases as the salt-freezing cycle progresses. Following the development trend of the cracks, concrete cracks can be divided into three categories: 0–40, 40–100, and 100–150 μm. The mass loss increases significantly, and the change of relative dynamic elastic modulus decreases in concrete with an initial crack compared with the intact concrete. When the crack width is 80 μm, a maximum mass loss rate of 0.19% and a minimum relative dynamic elastic modulus of 75.81% can be obtained. These test results prove that crack and freeze-thaw coupling can influence each other and accelerate the failure of concrete. Overall, this study can serve as a basis for the durability design and life improvement of concrete structures.